(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The Same Completely Inclusive Faith with Its Principium of Natural Laws of the Compounding-Corresponding-Trinity Presents and Unfolds Through Different Ways and Methods in Science, Philosophy, Religion, etc.” (Abbreviated as Principium. clarify that: The particles not only have the distinction between Commonality Particles and Individuality Particle; any particle compounding and corresponding, also have four major natural standpoint- attributes. Among them, “The Commonality Particle” consistently demonstrate higher stability than “The Individuality Particle” through compounding and corresponding. Similarly, the destruction of “The Commonality Particles” would cause greater harm to humans and nature, potentially even leading to human destruction. Only by adhering to “The Three Great Natural Complementary Laws” of Principium, can humans expand their lives and human society with clarity of mind, saving time and effort while ensuring safe operations